The Manufacture of Cold Storage with 10 Kg Capacity - Harwika; Ihsan; Irwansyah Syam; Rudiman Ritonga (Jurnal Inotera, 2023)
Indonesia is one of the maritime countries so that most of Indonesia's territory is the sea, which is rich in marine product; fish is one of the marine products. Fish is a commodity that is not durable and easily damaged if placed in open place. The main causes of fish damage include the activity of microorganisms and bacteria in the fish meat, where at room temperature bacteria and microorganisms can multiply rapidly. Therefore, the author makes a cold storage cooling system with a 10 kg capacity, which can be used to cool the fish caught by fishermen so that the quality and quality of the fish is still fresh to consumers or buyers so that can increase the selling price of fish caught by fishermen in South Aceh Regency. The cold storage manufacturing method is carried out with the initial process of measuring, cutting, welding, drilling, joining, vacuuming and electrical installation. The tools used in the process of making cold storage are welding machines, acetylene welders, cutting grinders, rubbing grinders, measuring elbows, meter tubing cutters, vacuum pumps, digital scales and clam meters. The materials used are angle iron, cold storage boxes, electrodes, relays, MCBs, elbows, and thermostats. The benefits generated by the manufacture of cold storage are to cool fish and increase knowledge of how the system works in cold storage for students of the South Aceh Polytechnic. The results of the cold storage trial for 30 minutes operate with an outside cold storage temperature of 270C and a cold storage temperature of -200C.